A fabrication method of continuous aero-model for high chimney. (December 2021) - Wang, Lei; Shi, Fen; Chen, Kai; Tang, Yi; Hao, Wei
Abstract: Wind tunnel test by aero-model is an accurate way to evaluate the performance of high-flexible structures under wind load, and the fabrication of aero-model is an important step in this work. Taking a circular section industrial chimney as an example, this study introduces a new method for making the aero-model with continuous shell. The continuous model in this paper is made by DEVCON plastic steel liquid, and the main fabrication process can be briefly summarized in the following steps. Firstly, the inner mold is made with gypsum and the outer mold is carved out of Plexiglas, with the gap width between the inner and outer mold precisely designed in this step. Secondly, the DEVCON liquid is infused into the gap; and finally, the molds are removed after the glue cured, and the aero-elastic model is now complete. Structural dynamic properties, such as frequencies, mode shapes and damping ratio, were measured after making the aero-model. Test results show that the model's dynamic properties are consistent with the actual chimney. After the continuous model is made, the wind-induced response can be simulated by conducting a reasonable wind tunnel test. The advantages of the proposed method are a short fabrication period, low cost, and high precision. Moreover, this method is applicable to a variety of cross-sections of high chimneys, regardless of whether the section shape is circular or not. This study can provide a new method for the design and fabrication of continuous aero-model of high chimneys.